Primary Open Angle Glaucoma - Yulia Puspita Sari; Najwa Khalisa (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Glaucoma is a group of neurooptic diseases that has one feature in the form of progressive optic nerve damage caused by increased intraocular pressure, characterized by abnormalities or atrophy of the optic nerve papillae, the presence of glaucomatous excavations, as well as visual field disturbances and blindness. This pattern of peripheral vision loss can also be a distinguishing characteristic from other forms of vision loss. Glaucoma is the second leading cause of blindness for more than 70 million people worldwide. Bilateral blindness occurs in an estimated 10%. In Indonesia, the prevalence of glaucoma is 0.46%. This proves 4 to 5 out of 1,000 people suffer from glaucoma. Risk factors for acute glaucoma are age over 40 years, a family history of glaucoma. For certain types of glaucoma, family members with glaucoma have a 6 times greater risk of developing glaucoma.